Cimarron Hotel Has Colorful History (Albuquerque, NM Albuquerque Journal, 1989)
This article is about the history of the St. James Hotel in Cimarron, New Mexico.
Newspaper article
Mater List Item # 13
File location is in the New Mexico File Cabinets
Keywords: Lambert, Henri; Lincoln, Abraham -- President of the United States; Grant, Ulysses S; Ketchum, Blackjack; Earp, Wyatt; Cody, Buffalo Bill; Oakley, Annie; Remington, Federic; Grey, Zane; Wallace, Lew; Allison, Clay; Sitzberger, Ed; Cooley, Jaque Littlejohn; St. James Hotel; Hotels; Museums; Gunslingers; Old West; History; Ghost Stories; Ghosts; Psychics; Cimarron, New Mexico; Santa Fe Trail